Labour Market Adjustments to Population Decline - Timon Hellwagner; Enzo Weber (ZBW - Leibniz Information Centre for Economics, 2021)
According to demographic projections, advanced economies will face population decline in the years and decades to come, particularly among working-age. Despite this impending profound transition, there is little empirical evidence of corresponding labour market implications. Tackling this shortcoming from a historical macroeconomic point of view, we compiled a new dataset for nine advanced economies, covering demographic and labour market variables on an annual basis from 1875 to 2016. By using a panel smooth transition VAR (PSTVAR), we analyze macroeconomic labour market interdependencies while simultaneously exploiting the cross-country variation to identify non-linearities of these interdependencies conditional on the demographic regime, that is periods of population growth or decline. Our results suggest that labour market adjustments to population shocks are, in fact, non-symmetrical. Most notably, labour supply shortages are mitigated by an increased participation rate, largely recovering the pre-shock employment level. Also, investments recover more strongly compared to periods of population growth. We find no clear effects on the unemployment rate and wages
Keywords: J11; J21; J31; E24; 330; population decline; labour market research; historical dataset; panelsmooth transition VAR